Change of Quadrupole Moment upon Excitation and Symmetry Breaking in Multibranched Donor‐Acceptor Dyes. Issue 15 (3rd July 2020) - Szakács, Zoltán; Tasior, Mariusz; Gryko, Daniel T.; Vauthey, Eric
Abstract: Upon photoexcitation, a majority of quadrupolar dyes, developed for large two‐photon absorption, undergo excited‐state symmetry breaking (ES‐SB) and behave as dipolar molecules. We investigate how the change of quadrupole moment upon S1 ←S0 excitation, Δ Q, influences the propensity of a dye to undergo ES‐SB using a series of molecules with a A ‐ π ‐D ‐ π ‐A motif where D is the exceptionally electron‐rich pyrrolo[3, 2‐b]pyrrole and A are accepting groups. Tuning of Δ Q is achieved by appending a secondary acceptor group, A', on both sides of the D core and ES‐SB is monitored using a combination of time‐resolved IR and broadband fluorescence spectroscopy. The results reveal a clear correlation between Δ Q and the tendency to undergo ES‐SB. When A is a stronger acceptor than A', ES‐SB occurs already in non‐dipolar but quadrupolar solvents. When A and A' are identical, ES‐SB is only partial even in highly dipolar solvents. When A is a weaker acceptor than A', the orientation of Δ Q changes, ES‐SB is observed in dipolar solvents only and involves major redistribution of the excitation over the D ‐ π ‐A and D‐A' branches of the dye. Abstract : The propensity of centrosymmetric multibranched dyes to undergo symmetry breaking was controlled by tuning their change of quadrupole moment upon excitation, Δ Q . This was achieved by varying the length, as well as the strength, of the acceptor arms around the donor core.